Preparation, sensory evaluation and effectiveness of Philippine Tree Fern (Cyathea contaminans) as anti-spasm oil - Mustacisa-Lacaba, M. M.; Dejarme, A. B.; Albina, M. B. (International Journal of Agricultural Technology, 2021)
Cyathea contaminans is an endemic fern which is popularly used as an ornamental plant in the Philippines, its medicinal value is rarely publicized though its chemical components such as ecysdteroids, triterpenoids, and lycodine alkaloid are linked to cure contusions, strains, and swelling with antioxidant, antidepressant, and photo-protectant effects. These facts led to the development of a research-based product, Cyathea contaminans as anti-spasm oil. The developed C. contaminans anti-spasm oil in three experiment set-ups was voluntarily assessed by 15 respondents for each set-up. The highest frequency count for the speed of efficacy was at set-up A (87.5% C. contaminans oil; 6.25% lavandula oil; 5% VCO, and 1.25% surfactant), which means that among the three set-ups, the respondents claimed that prepared product in set-up A had the capacity to produce an effect of less than 5 minutes. The solution prepared in set-up C (90% C. contaminans oil; 5% lavandula oil; 4% VCO, and 1% surfactant) had the highest longevity of efficacy with a time span of 5 to 15 minutes. Based on the statistical results, the developed C. contaminans anti-spasm oil prepared from three experiment set-ups had no significant differences in color, aroma, and texture. The three products were statistically comparable to each other. However, set-up C which contained 90% by volume of an active ingredients C. contaminans is considered to be the most effective based on the results of sensory evaluation. Laboratory tests and screening should be sought prior to commercialization to clinically prove the claim of the product preparation. This study would greatly contribute to agriculture for the economic value of Philippine tree fern, and develop the emerging technology that would cater such progress